Perlindungan Hukum bagi Konsumen atas Malpraktik Jasa Tukang Gigi - I Made Ari Yudistira; I Nyoman Putu Budiartha; I Made Minggu Widyantara (Warmadewa Press, 2021)
Number of dental artisans who practice beyond their authority limits. Even so, there are still many who go to dental artisans due to social disparities. There are many cases of violations that cause material and non-material losses to consumers, but health service providers are not responsible. This thesis discusses how to protect consumers and sanctions against perpetrators in the event of malpractice of dental artisans. The purpose of this study was to determine the protection for consumers in the event of malpractice of dental artisans and to know the sanctions against perpetrators of malpractice in dental artisan services that harm consumers. The type of research used is the type of normative legal research, the discussion is carried 0111 by examining legal materials. Analysis of legal materials uses extensive and restrictive interpretations, namely expanding and narrowing the meaning of a law, in addition to using descriptive analysis, namely the exposure of research results. Based on the results of the research, the legal regulation of consumer protection against malpractice of dental artisans which is regulated in the UUP K, the rights of every consumer in Article 4. Dental artisans as business actors have the obligation to comply with laws in this case regarding duties and authorities. Meanwhile, legal sanctions for perpetrators can be divided into 3, namely administrative, civil and criminal sanctions. Therefore, the government needs to carry out regular monitoring of cases like this in the direct field